Impact of Information Communication Technology (ICT) on Students Academic Performance in Public Secondary Schools in Nigeria - Niyi Jacob Ogunode; Oigoche Lilian (Researchparks Publishing, 2022)
Information communication is vital for the realization of educational objectives. It plays a critical role in the implementation of school programs. It is useful for school administrators, teachers and students. This paper examined the impact of information communication on students’ academic performance in public secondary schools in Nigeria. Secondary data were employed to provide empirical facts for the points raised in the paper. This study concludes that information communication technology (ICT) enhances academic performance of students, improves learning programme of students, and makes learning programme fast and flexible. The paper also established that students that are ICT literate perform better than those without ICT skills in term of online learning. The paper identified factors preventing public secondary schools students from effectively using ICT for their academic work to include inadequate ICT facilities, poor implementation of ICT policies, unstable internet services, unstable electricity, high cost of ICT facilities, poor ICT literacy among teachers and students and high cost of internet services.